CORROSION BEHAVIOUR OF CLADDING MATERIALS OF RESEARCH REACTOR SPENT FUEL DURING WET STORAGE - Qureshi, A. H.; Hussain, N.; Arif, M.; Ahmed, E.; Akram, M.; Qazi, N. K. (The Nucleus, 2020)
The present investigations deal with the study of the effect of water chemistry of spent fuel storage bay on corrosion properties of cladding materials of research reactor. Coupons of four different alloys of stainless steel (SS 316) and aluminium alloys (Al 6063, Al 6061 and Al 1100) in form of discs were assembled on a rack forming galvanic couples and crevice sandwiches. The rack was immersed in the spent fuel storage bay for a period of one year exposure. The monthly inspection of specimens was conducted out based on visual observation and photography. The analyses of water were done on weekly basis. After exposure of one year the rack was withdrawn and disassembled in the laboratory. The surface of each individual coupon was observed visually and by means of optical microscope. Visual observation revealed relatively more deposits of scale on aluminium samples in the galvanic couples compared to stainless steel (SS) samples. In the crevice sandwiches (Al+Al) both upper and lower samples were found almost identical with respect to scale deposits. The microscopic observations showed no pitting on any sample except at selective areas only in contact with ceramic spacers.